A Review of Research on Power Battery Closed-Loop Supply Chains from the Perspective of Supply Chain Management Theory - Hongmei Ma; Yingjie Xiong (Economics and Public Policy, 2026)
Driven jointly by carbon neutrality strategies and the rapid expansion of the new energy vehicle (NEV) industry, the large-scale retirement of power batteries has rendered resource circulation and environmental pollution problems increasingly urgent, and the power battery closed-loop supply chain (CLSC) has accordingly emerged as a frontier subfield of supply chain management research. Adopting supply chain management theory as the analytical perspective, this paper systematically reviews domestic and international literature published between 2001 and 2025. After clarifying the theoretical foundations—circular economy theory, extended producer responsibility (EPR), transaction cost economics, and contract theory—it synthesizes research progress along six thematic dimensions: recycling channel selection, pricing and contract coordination, echelon (second-life) utilization, government policy intervention, social preference behavior, and second-hand market competition, followed by a critical assessment along the three dimensions of theory, method, and context. The review finds that the theoretical paradigm of this field has shifted from static efficiency orientation toward dynamic resilience, greening, and intelligence orientation, and that a preliminary multidisciplinary, multimethod, and multiobjective research framework has taken shape; however, problems remain prominent, including unrealistic model assumptions, the absence of dynamic evolution characterizations, superficial treatment of sustainability mechanisms, and the disconnection between digital technologies and management science. Accordingly, this paper proposes six operationalizable future research agendas—dynamic multiperiod modeling, behavioral closed-loop supply chains, the integration of digital technology and governance, supply chain resilience, multiobjective optimization under carbon constraints, and cross-chain collaborative governance—to inform subsequent theory building and practical innovation.